O Plano Educacional Individualizado (PEI) na promoção da educação inclusiva: perspectivas docentes em escola pública paulista - Costa, Vitória Costa (Universidade Federal de São Carlos, 2025)
The increase in enrollment of children and adolescents with disabilities in Brazil indicates advances in inclusive education, a perspective that is still developing in our educational reality due to persistent barriers. The study aimed to analyze the process of elaboration, implementation and monitoring of the Individualized Educational Plan (PEI) by elementary and high school teachers in a public school in São Carlos - SP, based on legislation, in government guidelines and in the daily teaching work. A case study was developed through observations and semi-structured interviews with six teachers, examining the data with the aid of Content Analysis technique. The results show that PEI is essential for inclusion, but faces difficulties such as overwork, numerous classes, lack of training, lack of professionals and low family participation. To improve the effectiveness of PEI, collective actions are needed with clear legislation, continuous training, institutional support, family involvement and collaboration between teachers and managers.
The Individualized Educational Plan (IEP) in the promotion of inclusive education: teaching perspectives in São Paulo State public school
Keywords: Plano Educacional Individualizado; Educação Especial; Educação Inclusiva; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades